Strengthening Social Morality through the Qur'anic Discourse on LGBT: A Comparative Exegetical Study of Tafsir al-Qur'an li al-Shabab and Tafsir Marah Labid - Rohmat, Nur; Mufid, Abdul; Arif, Mohammad; Mahmudi, Ahmad (QiST: Journal of Quran and Tafseer Studies, 2025)
LGBT is a sexual orientation that does not represent the tendency of the majority of people, but rather a phenomenon that appears outside the general pattern of sexual orientation. The phenomenon will be viewed from the perspective of the Qur'an, the holy book of Muslims. This research uses the method of tafsir maudhu'i al-Farmawi by looking at the interpretation of female scholars, Fātin al-Falakī "Tafsīr al-Quran li al-Shabāb" and Tafsīr Marāh al-Labīd by Nawawī al-Bantanī, a mufassir born in Tanara, Banten, who is well known among the Nusantara Pesantren. This research analyzes five verses related to GBT behavior, namely QS. al-Shu'arā': 165-166, al-Naml: 54-55, al-Ankabūt: 38-30, al-A'rāf: 80-81, and QS. al-Nisā': 119. As a result, both Mufasirs condemn LGBT behavior, which in the Quran is described by the terms Ata'tūna al-Dukrāna, Fākhishah, and Taghyīr Khalq Allah. However, both only discuss the gay, bisexual, and transgender (GBT) aspects without explicitly touching the lesbian aspect. Preventive measures to prevent GBT behavior can be done by avoiding promiscuity, keeping the eyes and honor by dressing modestly and in accordance with Sharia values, getting married, and social sanctions through social control from elements of society.